Oronzio Maldarelli papers - Maldarelli, Oronzio, 1892-1962.
Correspondence, articles, press releases, curriculum, exhibition catalogs, business records, clippings, sketches, designs, photographs, and other papers relating to Maldarelli's career and commissions as a sculptor and educator. Documents his years as a teacher at Sarah Lawrence College and Columbia University as well as his work with directors of museums throughout the United States. Includes Maldarelli's designs for jewelry. Correspondents include artists such as Walker Hancock, Peppino Mangravite, and William Zorach, and Maldarelli's wife, Tillie Maldarelli.
Sculptor and educator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Hancock, Walker, -- 1901-1998 -- Correspondence; Maldarelli, Tillie, -- approximately 1892-- -- Correspondence; Mangravite, Peppino, -- 1896- -- Correspondence; Zorach, William, -- 1887-1966 -- Correspondence; Columbia University -- Faculty; Sarah Lawrence College -- Faculty; Jewelry -- Design; Museums -- United States; Sculpture; Educators; Sculptors